Analysis of Factors Affecting Community Participation Expectations on Sustainability Urban Farming in Jakarta City - M. Noor Salim; Edi Wahyu Wibowo; Darwati Susilastuti; Tungga Buana Diana (GoAcademica Research & Publishing, 2022)
To meet the nutritional needs of the people of Jakarta, urban agriculture is one of the food supply solutions. This study analyzes community expectations for participation in sustainable urban agriculture in Jakarta. The latest developments of this study provide results on the impact of economic, health and environmental variables on people's expectations for the sustainability of urban agriculture in Jakarta. The novelty of this study is that it considers the theme of the study, namely the inhabitants of the city of Jakarta, engaged in urban agriculture, a total of 112 respondents. The results of this study indicate that economic, health and environmental variables, simultaneously or in part, positively influence the expectations of community involvement in the sustainability of urban agricultural activities in the city of Jakarta. Based on these findings, it can be said that the expectation of community engagement in sustainable urban agriculture in Jakarta translates into greater productivity, knowledge, skills, awareness and understanding of the existence of clear regulations. The corrected R-square value is 0.704 based on the results of the coefficients that determine the impact of economic, health and environmental factors on community participation expectations in the sustainability of urban agriculture in Jakarta. In other words, 70.4% of community participation expectations in urban agriculture depend on economic factors, while health and other environmental factors depend on other factors. Expectations for community involvement in sustainable urban agriculture are already high and Jakarta's food security can be ensured later.